2019
DOI: 10.1103/physrevlett.122.068002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Self-Propelled Particle in a Harmonic Trap

Abstract: The dynamics of an active walker in a harmonic potential is studied experimentally, numerically and theoretically. At odds with usual models of self-propelled particles, we identify two dynamical states for which the particle condensates at finite distance from the trap center. In the first state, also found in other systems, the particle points radially outward the trap, while diffusing along the azimuthal direction. In the second state, the particle performs circular orbits around the center of the trap. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 17 publications
2
161
0
Order By: Relevance
“…Hexbug body is supported by twelve flexible legs that all bends slightly backwards. When turned on, the vibration motor sets Hexbug into forward hopping motion on a solid (PMMA) substrate [46,47]. As shown in Fig.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Hexbug body is supported by twelve flexible legs that all bends slightly backwards. When turned on, the vibration motor sets Hexbug into forward hopping motion on a solid (PMMA) substrate [46,47]. As shown in Fig.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Typically these are hoppers with a Janus-like body or with tilted legs. In order to achieve self-propulsion, these macroscopic bodies are either placed on a vibrating table or are equipped with an internal vibration motor ("hexbugs") 23 . It has been shown that the dynamics of these hoppers is well described by active Brownian motion with inertia [24][25][26] .…”
Section: A Generalmentioning
confidence: 99%
“…These motions are only virtually damped. Another important realization are granulates made self-propelling on a vibrating plate [13][14][15][16][17][18][19][20][21][22] or equipped with an internal vibration motor 23 where it has been shown that the active Langevin model indeed describes their dynamics well [24][25][26] . Further examples for self-propelled particles with inertia range from mini-robots 27,28 to macroscopic swimmers like beetles flying at water interfaces 29 and whirling fruits self-propelling in air 30 .…”
Section: Introductionmentioning
confidence: 99%
“…For example E. Coli bacteria runs for some time along a straight line and then tumbles to randomly choose a new direction of run [35]. In the last few years there has been a lot of interests in studying RTPs at the individual level as they show interesting phenomena like, accumulation near boundaries [36][37][38], clustering [39][40][41], passive to active transition [42,43], climbing against the hill [44], Kramer's escape problem [45] etc.…”
Section: Introductionmentioning
confidence: 99%